A Portable Negative Pressure Isolation System as a Solution to Minimize Exposure of Health Care Providers to Infectious Pathogens. Issue 8 (August 2022) - Economopoulos, Konstantinos P.; Fearis, Paul; Simmons, W. Neal; Richardson, Eric S.; Montgomery, Sean P.
The COVID-19 pandemic has resulted in the exposure of many surgeons and healthcare providers (HCPs) to disease given high patient loads and limited availability of negative pressure rooms. For these reasons we pursued the development of a portable patient isolation system (COVIAGE™ by iSolace, Inc.) that can be used to contain patients with respiratory illness and minimize the exposure of HCPs. COVIAGE™ is comprised of a reusable aluminum frame, a disposable thermoplastic polyurethane tent and a HEPA filtration/ventilation system (HVAC) utilizing two inline filters. The efficacy of filtration was tested by comparing particulate concentration inside and outside of the device by an independent third party. Additionally, physician, nursing, and respiratory tasks were performed initially on simulated patients and then on intubated patients in the ICU. The system attained a verified filtration efficiency greater than 99.999% for an average 0.3-μm size particulates. Simulation testing revealed that most common physician, nursing, and respiratory tasks could be completed in the device, including endotracheal intubation. Emergency removal of the device can be accomplished in 8.8 ± 2.8 seconds. The reusable aluminum frame allows for simple attachment to the bed, and adaptability to different types and sizes of beds/stretchers. An emergency use authorization was granted by the FDA. The device created results in a portable negative pressure isolation system that can be placed over the patient's bed to contain aerosols during high aerosol generating procedures, transportation of patients or for total patient care in environments where negative pressure rooms are not available.